Analisis Strategi Pengamanan Objek Vital Nasional Studi Kasus: Kota Tua Jakarta - Dewanti, Handaru Faradila; Wisnu Aji Patria Perkasa, Arsenius (UNES Law Review, 2024)
Based on the Decision of the Minister of Tourism of the Republic of Indonesia Number KM.70/UM. 001/MP/2016 regarding the Determination of National Vital Objects in the Tourism Sector, the Kota Tua tourist area has been designated as a National Vital Object. As one of the national vital objects, it certainly requires security strategies to protect historical artifacts, tourists, and individuals working in Kota Tua. Unfortunately, cases of crimes such as ATM theft, pickpocketing, and impersonation of police officers still occur. These security disturbances can create feelings of insecurity for individuals in the Kota Tua area. One security strategy that can be applied is the concept of crime prevention through environmental design (CPTED). The metode used in this research is a qualitative approach with descriptive research. Data collection is done through observation, interviews, and literature studies. This research will be conducted in Kota Tua, West Jakarta. The results of this study indicate that the Kota Tua Management Unit has implemented crime prevention through environmental design with three component which is access control, surveillance, and territoriality, despite some shortcomings.